A promising strategy for mechanically modified wheat flour by milling of wheat endosperm. (March 2022) - Tian, Xiaoling; Wang, Zhen; Wang, Xiaoxi; Sun, Binghua; Ma, Sen; Wang, Fengcheng
Abstract: A planetary mill was used to grind pure endosperm granule flour using both low-temperature control and normal modes. Particle size distribution, microstructure, pasting characteristics, water absorption indexes, solubility indexes, in vitro digestibility, and thermal characteristics were determined for samples ground for different lengths of time. The resulting flour had D50 below 30 μm and crushed starch content of 8%. Better dispersion of protein and starch was achieved for low temperature grinding and increased grinding time. Independently of temperature, milling decreased peak viscosity, trough viscosity (from 2339 to 1896 cp), and final viscosity (from 3947 to 3535 cp). The water solubility also decreased. There was also a decrease in the enthalpy ( ΔH ) of gelatinization, and the enthalpy ( ΔH ) of gelatinization at low temperature was higher at normal temperature. The rapidly digestible starch content was lower and slowly digestible starch content was higher in flour compared with raw material, and the changes in the low and normal modes showed opposite trends, probably influenced by the starch granules surface-protein and starch amorphous regions. The above results suggest that the functional properties of wheat flour were significantly altered by planetary ball milling at low speed and short duration (<200 rpm, <30 min), suggesting potential strategies to expand the flour food applications. Graphical abstract: Image 1 Highlights: Low speed ball milling method has been applied to prepare mechanically modified flour (MMF). Pasting properties of MMF are significantly affected by the ball milling time. MMF exhibited little higher slowly digestible starch and lower resistant starch contents as compared to raw material. Ball milling needs to break the gluten and expose the starch granules before causing starch damage